(untitled) (Моделювання, керування та інформаційні технології, 2025)
The article presents the developed unmanned robotic complex for evaluation of small arms fire. The complex is designed for effective training of soldiers and officers in shooting at close and long distances (20 ¸ 1500 m.). The operating principle of the system is briefly described and technical characteristics are given. The complex is equipped with a hydro meteorological station for correcting shooting in accordance with the ballistic characteristics of the projectile during shooting. The shaped target is made of polymer carbon plastic material and it has a long service life. The software for unmanned control of the robotic complex has been developed. It is shown that the proposed unmanned robotic system has significant advantages over foreign analogues.